(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
There is no denying that English is not only playing an important role in most regions of the world but also holding the leading role in the education and future careers of students in the era of 4.0 technology. To master English, writing skill is one of the indispensable skills. However, in learning writing process, English learners in general, and English majored sophomores at Tay Do University in particular face many obstacles. The study was conducted to identify the challenges facing second-year students. The participants were 84 English majored sophomores. The survey tool used to collect the data was the questionnaire. The study identified the challenges in writing as vocabulary, grammar, and background knowledge.